Octopus‐Inspired Soft Arm with Suction Cups for Enhanced Grasping Tasks in Confined Environments. (22nd October 2019) - Mazzolai, Barbara; Mondini, Alessio; Tramacere, Francesca; Riccomi, Gianluca; Sadeghi, Ali; Giordano, Goffredo; Del Dottore, Emanuela; Scaccia, Massimiliano; Zampato, Massimo; Carminati, Stefano
Abstract : Soft Robotics : In article number 1900041, Barbara Mazzolai, and co‐workers present an octopus‐inspired soft arm with suction cups to retrieve objects from confined environments. The proposed solution benefits both from the arm conformability and the improved grasping force generated by suction cups. Starting from the investigation of the octopus' manipulation and sucker‐based grasping capabilities, as well as its fetching and reaching movements, the artificial soft arm is able to grasp varied and complex‐shaped objects, to move in air, water and oil, and retrieve items in constrained environments, under pressure'.